ANALISA PERHITUNGAN BIAYA TUNDAAN LALU LINTAS PADA SIMPANG TIGA JALAN JUANDA DAN JUANDA 8 KOTA SAMARINDA - Dedy Mandala R, Dwi (KURVA S JURNAL MAHASISWA, 2012)
ABSTRACT            The purpose of research is to know cost analysis calculation of traffic delays Simpang" Juanda Three Way and Juanda 8 Samarinda. The research was done from June 2012 until August 2012 (8 weeks). The time for the observation consist of three part of time, the first 07.00 am - 09.00 am, second 11.00 am - 01.00 pm, and the last 04.00 pm - 06.00 pm. The result of the research are the calculation of vehicle operating cost that occur when traffic conditions stabilized is Rp. 15.182,-/ km/ vehicle and traffic delay caused a lot of trips up there so it raises the cost of delay, large costs on average delay during rush hour is Rp.36.783.,-/ km/ vehicle.Keywords: Cost Analysis, Vehicle Operating Cost